Restructuring Uganda’s Coffee Industry: Why Going Back to the Basics Matters - Baffes, John (World Bank, Washington, DC, 2012)
After experiencing a boom during the mid-1990s, the performance of Uganda's coffee industry has been disappointing. Most existing analyses see the sector's problems as quality deterioration, poor marketing position in the global market, weak regulatory framework, and poor infrastructure. Recommendations range from setting up a coffee auction to increasing the share of specialty coffees. This paper concludes that such advice has been largely inconsistent with the stylized facts of the Ugandan coffee industry. It argues that the coffee wilt disease and the effectiveness of the coffee replanting program are the two key issues on which policymakers and the donor community should focus their activities and allocate their resources.